A positive electrode material and a battery comprising the positive electrode material

By using polysonic single crystal positive electrode material, the problem of difficult to balance the circulation performance and rate performance of the positive electrode material in the prior art is solved, and the high capacity, energy density, cycle performance and rate performance of the battery are achieved, and the safety performance and thermal stability of the battery are improved.

CN115249800BActive Publication Date: 2025-05-02ZHUHAI COSMX POWER BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210903868.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-28
Publication Date
2025-05-02
Estimated Expiration
2042-07-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials are difficult to take into account both the circulation performance and the rate-to-magnetic performance. The secondary spherical materials have poor circulation and are prone to shattering, and the rate-to-magnetic performance of single crystal materials is poor and have a high safety hazard.

Method used

A polysingular crystal positive electrode material is used, which is formed by nesting several primary particles, meets a specific particle size relationship, has high thermal decomposition temperature, low temperature rise, excellent cycling performance and rate performance, and enhances surface stability through the cladding layer.

Benefits of technology

It achieves the balance of high capacity performance, energy density, cycle performance and rate performance of the battery, while improving the safety performance and thermal stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115249800B_ABST
    Figure CN115249800B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode material and a battery including the positive electrode material. The positive electrode material of the present invention has a special morphology of a poly-single crystal, the material is not easy to break after rolling, the compaction density is high, the surface of the poly-single crystal particles is relatively smooth, the contact with the conductive agent is good, it is conducive to the transmission of lithium ions, the initial DCR value is low, and the temperature rise of the material during the charge and discharge cycle is low; the poly-single crystal particles have good structural stability, can ensure excellent cycle performance, high voltage cycle performance is stable, and safety performance can be improved. Furthermore, the surface of the positive electrode material is coated with an inert metal compound, which can effectively prevent the electrolyte from damaging the surface of the positive electrode material, and enhance the surface properties and structural stability of the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular, relates to a positive electrode material with a special morphology structure and a battery comprising the positive electrode material. Background Art

[0002] Currently, the cathode materials for lithium-ion batteries on the market are mainly divided into two categories: single crystal and secondary sphere. Single crystal materials are widely used in soft-pack lithium-ion batteries due to their good cycle performance, high compaction density, and excellent high voltage resistance, but they also have the disadvantages of relatively low gram capacity and poor rate performance. Secondary sphere materials are mostly aggregates of spherical primary particles, that is, secondary sphere particles formed by the agglomeration of primary particles. This type of secondary sphere has the characteristics of high gram capacity and good rate performance, but the agglomerated particles of secondary spheres are easy to break during rolling, and have the disadvantages of low compaction density and poor cycle performance.

[0003] After research, it was found that the poor cycle of secondary sphere materials is mainly due to the repeated expansion and contraction of the crystal volume of secondary particles or agglomerated single crystals during the battery charging and discharging process, and the expansion and contraction directions of primary particles in the agglomerated secondary spheres are different or even opposite, resulting in stress between primary particles in the secondary spheres, and the primary particle interface may be pulverized in the later stage of the cycle, some primary particles are inactivated, the battery capacity decays quickly, and the cycle becomes poor; compared with secondary sphere agglomerates, single crystal materials have relatively less stress and excellent cycle performance. However, due to the long path of lithium ion migration, its rate performance is poor.

[0004] Moreover, in the prior art, the positive electrode material is crystallized into a single crystal form of primary particles, so that the material is not easy to break after rolling. However, the disadvantage of this technology is that after the material is prepared into a positive electrode sheet, the particles are in a single crystal state, and the contact between the electrolyte and the single crystal particle interface is not sufficient, which will lead to increased battery polarization and a larger initial DC internal resistance DCR during the battery charging and discharging process. In addition, the temperature rise of single crystal materials at different rates will be relatively high, which will cause certain safety hazards to the battery and also limit the use of single crystal materials in certain fields.

[0005] At the same time, high-nickel ternary cathode materials have high specific capacity and low raw material cost, and have been attracting attention from the new energy industry in recent years. However, in traditional battery systems, ternary cathode materials will undergo drastic structural changes and interface side reactions under high voltage and high temperature, which brings huge challenges to practical applications. The results of current research show that the higher the nickel content in the ternary cathode material, the worse the thermal stability of the material and the worse the safety.

[0006] The thermal stability of materials is directly related to the safety performance of batteries, and the thermal decomposition temperature of positive electrode materials is often a key factor affecting thermal runaway of batteries. Studies have shown that the higher the nickel content in ternary materials, the worse the thermal stability and the worse the safety of the battery. Summary of the invention

[0007] In order to improve the deficiencies of the prior art, the purpose of the present invention is to provide a multi-single crystal positive electrode material and a battery comprising the positive electrode material. The positive electrode material comprises a plurality of particles having a multi-single crystal morphology, and the positive electrode material having particles having a multi-single crystal morphology has a high thermal decomposition temperature; the positive electrode material can have a lower temperature rise, higher thermal stability and high-temperature cycle stability, and the positive electrode material also has the characteristics of low internal resistance; the positive electrode material has a higher charge and discharge voltage and specific capacity characteristics, and the use of the positive electrode material can enable the battery to have higher capacity performance and energy density. The use of the positive electrode material of the present invention can also enable the battery to have both cycle performance and rate performance.

[0008] The object of the present invention is achieved through the following technical solutions:

[0009] The present invention provides a positive electrode material, the positive electrode material comprises a plurality of particles having a polymerized single crystal morphology, the particles having a polymerized single crystal morphology are formed by nesting a plurality of primary particles; the positive electrode material satisfies the relationship shown in the following formula 1:

[0010] D 50 3 =K×n×d 50 3 Formula 1

[0011] Wherein, K is the coefficient, and its range is: 0.2≤K≤2; n is the number of primary particles, and its range is: 2≤n≤500; D 50 is the median particle size of the positive electrode material, in μm; d 50 It is the median particle size of primary particles, in μm.

[0012] The present invention provides a positive electrode sheet, which comprises the positive electrode material mentioned above.

[0013] The present invention provides a battery, which comprises the above-mentioned positive electrode material or the above-mentioned positive electrode sheet.

[0014] Beneficial effects of the present invention:

[0015] The present invention provides a positive electrode material and a battery including the positive electrode material. The positive electrode material of the present invention has a special morphology of a poly-single crystal, the material is not easy to break after rolling, the compaction density is high, the surface of the poly-single crystal particles is relatively smooth, and the contact with the conductive agent is good, which is conducive to the transmission of lithium ions, the initial DCR (direct current resistance) value is low, and the temperature rise of the positive electrode material during the charge and discharge cycle is low; the poly-single crystal particles have good structural stability, can ensure excellent cycle performance, high voltage cycle performance is stable, and safety performance can be improved. Furthermore, the surface of the positive electrode material is coated with an inert metal or non-metallic compound, which can effectively prevent the electrolyte from damaging the surface of the positive electrode material, and enhance the surface properties and structural stability of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the SEM electron microscope image of the ternary material of Example 1 (multi-single crystal).

[0017] Figure 2 This is the SEM electron microscope image of the ternary material of Comparative Example 1 (secondary sphere).

[0018] Figure 3 It is a comparison chart of the cycle data of the batteries of Example 1 and Comparative Example 1.

[0019] Figure 4 This is the SEM electron microscope image of the ternary material of Comparative Example 2 (single crystal).

[0020] Figure 5 The graph shows the change in DC internal resistance of the batteries of Example 2 and Comparative Example 2 after 1200 cycles.

[0021] Figure 6 This is the SEM electron microscope image of lithium cobalt oxide after the first sintering of Example 3 (poly single crystal).

[0022] Figure 7 This is the SEM electron microscope image (single crystal) of lithium cobalt oxide after primary sintering in Comparative Example 3.

[0023] Figure 8 This is the SEM electron microscope image of lithium cobalt oxide after the first sintering of Comparative Example 4 (secondary sphere). DETAILED DESCRIPTION

[0024] [Cathode material]

[0025] As mentioned above, the present invention provides a positive electrode material, the positive electrode material includes a plurality of particles with a multi-single crystal morphology, the particles with a multi-single crystal morphology are formed by nesting a plurality of primary particles; the positive electrode material satisfies the relationship shown in the following formula 1:

[0026] D 50 3 =K×n×d50 3 Formula 1

[0027] Wherein, K is the coefficient, and its range is: 0.2≤K≤2; n is the number of primary particles, and its range is: 2≤n≤500; D 50 is the median particle size of the positive electrode material, in μm; d 50 It is the median particle size of primary particles, in μm.

[0028] According to an embodiment of the present invention, K is 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0.

[0029] According to an embodiment of the present invention, n is 2, 5, 10, 20, 50, 80, 90, 100, 120, 130, 150, 180, 200, 220, 230, 240, 250, 260, 280, 300, 320, 340, 350, 380, 400, 420, 430, 450, 480, 490 or 500.

[0030] According to an embodiment of the present invention, the particles with a multi-single crystal morphology in the positive electrode material are formed by the nesting of a plurality of primary particles. The nesting described in the present invention is not a core-shell structure. The core-shell structure has an obvious core structure and a shell structure, while the particles with a multi-single crystal morphology of the present invention are formed by the nesting aggregation of a plurality of primary particles, that is, one primary particle in the particles with a multi-single crystal morphology is connected and fused with a plurality of primary particles by an internal driving force to form a surrounding structure, for example, refer to Figure 1 .

[0031] According to an embodiment of the present invention, the several refers to one or more than two.

[0032] According to an embodiment of the present invention, the particles having a multi-single crystal morphology are formed by nesting 2-500 (such as 5-100) primary particles.

[0033] According to an embodiment of the present invention, the surface of the particles having a polymerized single crystal morphology is relatively smooth.

[0034] According to an embodiment of the present invention, the multi-single crystal morphology structure of the particles is different from the single crystal structure in the prior art, and is also different from the secondary spherical structure. The secondary spherical structure generally exists in ternary materials and needs to be treated with D 50The precursor with a diameter of more than 7 μm is synthesized and prepared, and the spherical particles formed by the secondary spherical particles known in the field of ternary materials are very regular. Secondary spherical particles can also be called polycrystalline materials. The primary particles of secondary spherical particles are very different from single crystals, quasi-single crystals and the polycrystalline single crystals of the present invention, and the growth mode is also different. The particles with polycrystalline morphology of the present invention are made of D 50 <7μm ternary material precursor (D 50 The growth of primary particles tends to grow in the direction of single crystallization. In order to avoid the complete formation of a single crystal dispersed structure, the present invention forms a multi-single crystal morphology structure by selecting a precursor and a doping modifier with a specific particle size and controlling the calcination temperature.

[0035] According to an embodiment of the present invention, the median particle size d 50 It is 0.1μm-3μm, for example, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm or 3μm.

[0036] According to an embodiment of the present invention, the median particle size D of the positive electrode material is 50 0.2μm-20μm, for example, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.1μm , 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, μm, 4μm, 5μm, 6μm , 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.

[0037] According to an embodiment of the present invention, the primary particles are ternary materials or lithium cobalt oxide.

[0038] In one embodiment, the chemical formula of the ternary material is Li a Ni1-x-y-p Co x M 1 y M 2 p O 2 ,0.95≤a<1.08,0.5≤1-xyp<1.0,0 <x≤0.3,0<y≤0.2,0<p≤0.005;M 1 Mn or Al, M 2 It is one or more of Mg, Sr, Ba, Y, W, Nb, and Mo. Preferably, 0.0005≤p≤0.005.

[0039] In one embodiment, the chemical formula of the lithium cobalt oxide is Li a Co 1-b M b O 2 , wherein M is one or more of Al, W, Mg, Ti, Zr, Y, Ce, Mo, 0.95≤a≤1.07, 0 <b≤0.1。

[0040] According to an embodiment of the present invention, the positive electrode material further comprises a coating layer, and the coating layer is coated on the surfaces of a plurality of particles having a multi-single crystal morphology.

[0041] According to an embodiment of the present invention, the mass proportion of the coating layer is 500ppm-5000ppm, for example, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1500ppm, 1800ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm or 5000ppm; that is, the mass of the coating layer accounts for 0.05-0.5wt% of the total mass of the positive electrode material, for example, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt% or 0.5wt%.

[0042] According to an embodiment of the present invention, the material forming the coating layer is a metal compound and / or a non-metal compound.

[0043] According to an embodiment of the present invention, the metal compound is at least one selected from aluminum oxide, tungsten oxide, molybdenum oxide, zirconium oxide and titanium oxide.

[0044] According to an embodiment of the present invention, the non-metallic compound is selected from boron oxide.

[0045] According to an embodiment of the present invention, the coating layer includes a first coating layer and a second coating layer, the first coating layer is coated on the surface of several particles having a multi-single crystal morphology, and the second coating layer is coated on the outer surface of the first coating layer, the first coating layer is a metal compound, and the second coating layer is a metal compound and / or a non-metal compound.

[0046] According to an embodiment of the present invention, in the differential scanning calorimetry (DSC) spectrum of the positive electrode material at a voltage of 4.1-4.4V, the starting exothermic temperature of the main exothermic peak is above 278°C, and the integrated area of ​​the main exothermic peak is below 98 J / g.

[0047] [Preparation of positive electrode materials]

[0048] The present invention also provides a method for preparing the above-mentioned positive electrode material, the method comprising the following steps:

[0049] Step S1: D 50 The ternary precursor with a particle size less than 7 μm, the lithium source and the doping modifier are uniformly mixed to obtain a precursor mixture;

[0050] Step S2: calcining the above-mentioned precursor mixture for the first time to prepare a multi-single crystal ternary positive electrode material.

[0051] According to an embodiment of the present invention, the method further comprises the following steps:

[0052] Step S3: adding the first coating agent to the above-mentioned positive electrode material, mixing at high speed, and heat treating at a constant temperature in an oxygen-containing environment to obtain a single-layer coated multi-single crystal ternary positive electrode material;

[0053] Step S4: The second coating agent is added to the single-layer coated poly-single crystal ternary positive electrode material obtained in the above step S3, mixed at high speed, and subjected to constant temperature heat treatment in an oxygen-containing environment, crushed and separated to obtain a double-layer coated poly-single crystal ternary positive electrode material.

[0054] According to an embodiment of the present invention, in step S1, the ternary precursor is Ni 1-x-y Co x M 1 y (OH) 2 , where 0.5≤1-xy<1.0, 0 <x≤0.3,0<y≤0.2。

[0055] According to an embodiment of the present invention, in step S1, the lithium source is selected from one or more of lithium hydroxide, lithium nitrate, lithium sulfate, lithium chloride, lithium carbonate, lithium phosphate, lithium fluoride, lithium acetate, lithium oxalate or lithium hydrogen phosphate;

[0056] According to an embodiment of the present invention, in step S1, the doping element of the doping modifier is preferably one or more of Mg, Sr, Ba, Y, W, Nb, and Mo, and the added amount of the doping element is 0-5000 ppm (excluding 0 ppm).

[0057] According to an embodiment of the present invention, in step S1, the molar ratio of the lithium source to the ternary precursor is 1.01-1.15:1.

[0058] According to an embodiment of the present invention, in step S1, the mixing is, for example, dry ball milling, the ball milling medium is zirconia balls or steel balls, the speed is 200-800 r / min, and the time is 3-6 h.

[0059] According to an embodiment of the present invention, in step S2, the first roasting is to increase the temperature to 400-600°C at 2-15°C / min and keep it for 1-6h, then increase the temperature to 700-800°C at 2-15°C / min and keep it for 2-12h, and finally increase the temperature to 800-920°C at 2-15°C / min and keep it for 2-16h, followed by natural cooling.

[0060] According to an embodiment of the present invention, in step S2, the material after the first calcination is crushed and separated to obtain a multi-single crystal ternary positive electrode material.

[0061] According to an embodiment of the present invention, in step S3, the first coating agent is a metal compound. The metal compound is at least one of nano-scale oxides, hydroxides or salts containing Al, Ti, Zr, Mo, and W, preferably nano-scale oxides or hydroxides of Al, Ti, and W. The mass of the first coating agent accounts for 0.05-0.50wt% of the mass of the multi-monocrystalline ternary positive electrode material.

[0062] According to an embodiment of the present invention, in step S3, the constant temperature heat treatment is to increase the temperature to 200-900°C at 2-15°C / min and keep the temperature for 3-16h.

[0063] According to an embodiment of the present invention, in step S4, the second coating agent is at least one of a metal compound and / or a non-metal compound. Wherein, the metal compound is at least one of a nano-scale oxide, hydroxide or salt containing Al, Ti, Zr, Mo, and W, preferably a nano-scale oxide or hydroxide of Al, Ti, and W. The non-metal compound is selected from boron oxide. Wherein, the mass of the second coating agent accounts for 0.05-0.50wt% of the mass of the multi-monocrystalline ternary positive electrode material.

[0064] According to an embodiment of the present invention, in step S4, the constant temperature heat treatment is to increase the temperature to 200-900° C. at 2-15° C. / min and keep the temperature for 2-16 hours.

[0065] The present invention also provides a method for preparing the above-mentioned positive electrode material, the method comprising the following steps:

[0066] Step S1, mixing a cobalt source, a lithium source and a doping modifier, sieving the mixture to obtain a mixed precursor material, sintering, crushing and sieving the mixed precursor material to obtain a primary sintered material, i.e., a poly-single-crystal lithium cobalt oxide positive electrode material;

[0067] In step S1, the sintering is carried out in an air atmosphere at a heating rate of 5°C / min to 730-750°C, and after maintaining for 1 hour, the heating rate is switched to 2°C / min to 980-1000°C, and maintained for 8-10 hours.

[0068] According to an embodiment of the present invention, in step S1, adding the step of screening can make the mixed bulk more uniform after screening, which can be more beneficial to the growth of multi-single crystals after sintering.

[0069] According to an embodiment of the present invention, the method further comprises the following steps:

[0070] Step S2, taking the first sintered material as raw material, adding the first coating agent and mixing to obtain a mixed material, sintering, crushing, and sieving the mixed material to obtain a single-coating-layer coated poly-single-crystal lithium cobalt oxide positive electrode material.

[0071] According to an embodiment of the present invention, the method further comprises the following steps:

[0072] Step S3, using the secondary sintered material in step S2 as raw material, adding a second coating agent and mixing to obtain a mixed material, sintering, crushing, and sieving the mixed material to obtain a double-coating-layer coated poly-single-crystal lithium cobalt oxide positive electrode material.

[0073] According to an embodiment of the present invention, in step S1, the cobalt source is one or more of cobalt tetroxide, cobalt oxide, cobalt hydroxide, cobalt carbonate or cobalt acetate, preferably cobalt tetroxide. 50 5-20 microns, preferably 8-12 microns.

[0074] According to an embodiment of the present invention, the lithium source in step S1 is one or more of lithium carbonate, lithium hydroxide, lithium chloride, lithium oxide or lithium nitrate, preferably lithium carbonate and / or lithium hydroxide.

[0075] In the mixture of step S1, the molar ratio of Li / Co is (1.02-1.07):1, preferably 1.05:1.

[0076] The addition amount of the doping element in the doping modifier in step S1 is 0-100000 ppm.

[0077] The doping modifier described in step S1 is a nano-scale oxide, hydroxide or salt of Al, W, Mg, Ti, Zr, Y, Ce or Mo. Preferably, Al, W, Mo, Mg or Zr is used.

[0078] According to an embodiment of the present invention, the first coating agent in step S2 is defined as above, wherein the mass of the first coating agent accounts for 0.05-0.50wt% of the mass of the multi-single-crystal lithium cobalt oxide positive electrode material.

[0079] According to an embodiment of the present invention, the second coating agent in step S3 is defined as above, wherein the mass of the second coating agent accounts for 0.05-0.50wt% of the mass of the multi-single-crystal lithium cobalt oxide positive electrode material.

[0080] [Positive electrode]

[0081] The present invention also provides a positive electrode sheet, which comprises the positive electrode material mentioned above.

[0082] According to an embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes the above-mentioned positive electrode material.

[0083] According to an embodiment of the present invention, when the positive electrode sheet is charged from a SOC of 10% to a SOC of 80% at a rate of 0.1C, in the differential scanning calorimetry analysis spectrum (DSC) of the positive electrode sheet, the starting exothermic temperature of the main exothermic peak is above 220°C, and the integrated area of ​​the main exothermic peak is below 98 J / g.

[0084] [Battery and its preparation]

[0085] The present invention also provides a battery, which comprises the above-mentioned positive electrode material or the above-mentioned positive electrode sheet.

[0086] According to the embodiment of the present invention, in this article, "80% SOC" means that when the battery is charged to a certain voltage at a specified rate, it will correspond to a capacity. When the ratio of the capacity corresponding to the voltage to the capacity corresponding to the cut-off voltage reaches 80%, the battery's state of charge (State of Charge, SOC) is 80%. The battery will have a "full charge state" when charging, that is, 100% SOC, and a corresponding "charge cut-off voltage" is set to ensure the safe use of the battery. In other words, the secondary battery composed of the positive electrode containing the above-mentioned positive electrode material is charged to the charge cut-off voltage within the range of reversible charge and discharge. The "full charge state" or "charge cut-off voltage" will vary due to different positive electrode materials or safety requirements. SOC = Q charge capacity / Q full charge capacity * 100%.

[0087] According to an embodiment of the present invention, in this article, the corresponding relationship between "SOC" and charging voltage and charging capacity is combined to obtain a positive electrode material at 10% SOC-80% SOC for research. Specifically, a series of batteries using the positive electrode material are charged to 2.8V-4.3V at a rate of 0.1C, wherein the preferred charging voltage interval is 0.1V, i.e., 2.8V, 2.9V, 3.0V, ..., 4.2V, 4.3V, and the corresponding charging capacity Q charging capacity at different voltages is recorded, wherein 4.3V is the charging cut-off voltage, and its corresponding capacity is the full charge capacity Q full charge capacity, and the ratio of the charging capacity to the full charge capacity at different voltages Q charging capacity / Q full charge capacity is calculated, thereby obtaining 10% SOC-80% SOC.

[0088] According to the present invention, it should be particularly noted that after the battery is charged to 10%-80% SOC, the positive electrode plate of the battery is immediately disassembled and DSC tested, preferably 50% SOC, 60% SOC, 70% SOC, 80% SOC, 90% SOC, 100% SOC.

[0089] The present invention provides a method for preparing the above-mentioned battery, comprising the following steps:

[0090] Step S1, weigh 100g of the above-mentioned multi-single crystal positive electrode material, conductive agent Super P, and binder PVDF in a weight ratio of 96:2:2 in order, mix them in 40g NMP, and obtain a uniform slurry by vacuum stirring, then evenly coat the slurry on the aluminum foil current collector, roll bake at 100°C in a 10m oven (rolling belt 2m / min), vacuum bake at 85°C for 20h, and then cold press and cut to obtain a positive electrode sheet containing a positive electrode lithium supplement material;

[0091] Step S2, weighing 100 g of artificial graphite: conductive agent Super P: CMC: SBR in a weight ratio of 95:2:1.5:1.5 in order, mixing them in 40 g of deionized water, and obtaining a uniform slurry by vacuum stirring, and then evenly coating the slurry on the copper foil current collector, rolling baking in a 100° C. oven (rolling belt 2 m / min), vacuum baking at 85° C. for 20 h, and then cold pressing and slitting to obtain a negative electrode sheet;

[0092] Step S3, stacking the positive electrode sheet, the negative electrode sheet, and the separator into a lithium-ion battery cell; placing the lithium-ion battery cell into a soft-pack battery package and injecting 1 mol / L lithium hexafluorophosphate (LiPF 6 ) of ethyl carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio), an electrolyte containing 2wt% vinylene carbonate (VC) and 3wt% 1,3-propane sultone (PS);

[0093] Step S4, after hot pressing, chemical formation, cold pressing, aging, secondary sealing, sorting and other steps, a lithium-ion battery using a multi-single crystal ternary positive electrode as a positive electrode active material is prepared.

[0094] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0095] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0096] The test of initial DC internal resistance in the following embodiments: 1. Stand for 10 minutes; 2. Discharge at 0.2C to a cut-off voltage of 2.75V; 3. Stand for 10 minutes; Place at the corresponding test temperature for a period of time until a stable state is reached (the shelf time must not be less than 2h), discharge with a certain pulse current for a certain time, and calculate the DCIR.

[0097] Example 1

[0098] (1) According to Li 2 CO 3 With D 50 Ni of 3-7μm (excluding 7μm) 0.65 Co 0.15 Mn 0.25 (OH) 2 According to the molar ratio of Li / (Ni+Co+Mn) of 1.05:1, a certain amount of nano-MoO was added after high-speed mixing at 400r / min. 3 and WO 3 , continue to mix at a high speed of 400r / min, where Mo 2 O 3 The amount of Ni added accounts for 0.65 Co 0.15 Mn 0.25 (OH) 2 The molar ratio of WO is 0.2%. 3 The amount of Ni added accounts for 0.65 Co 0.15 Mn 0.25 (OH) 2The molar ratio is 0.3%; the mixture is placed in a sagger and sintered for the first time in a box furnace, and oxygen is introduced as the sintering atmosphere. The synthesis is mainly carried out in three constant temperature zones, and the heating rate between each zone is 2℃ / min: the low temperature zone is kept at 400℃ for 1h; the medium temperature zone is kept at 700℃ for 2h; the high temperature zone is kept at 900℃ for 12h; then the box furnace is cooled naturally, the material is taken out, and it is crushed by air flow and passed through a 300-mesh screen to obtain a multi-single crystal ternary material;

[0099] In the poly-single-crystal ternary material, the number of primary particles n is 5-100, and the median particle size D of the positive electrode material is 50 The median particle size of primary particles is 4.08 μm. 50 0.2-1.5μm;

[0100] Satisfies the relationship shown in the following equation 1:

[0101] D 50 3 =K×n×d 50 3 Formula 1

[0102] Among them, K is 0.3-2.

[0103] The obtained multi-single crystal ternary material is mixed with nano-scale Al 2 O 3 Mix well, including Al 2 O 3 The mass ratio of the polysingle crystal ternary material is 1000ppm, and the second sintering is carried out. The temperature is raised to 600℃ at 2℃ / min in an oxygen atmosphere and kept for 10h. After cooling, a single-layer coated polysingle crystal ternary material is obtained. The above-obtained single-layer coated polysingle crystal ternary material is mixed with nano-scale WO 3 Mix well, including WO 3 The mass ratio of the single-layer coated multi-single crystal ternary material is 2000ppm, and the third sintering is carried out. The temperature is raised to 500℃ at 2℃ / min in an oxygen atmosphere and kept for 10 hours. After cooling, a double-layer coated multi-single crystal ternary material is obtained. The scanning electron microscope image is as follows Figure 1 shown.

[0104] (2) Weigh 100 g of the above-mentioned multi-single crystal positive electrode material, conductive agent Super P, and binder PVDF in a weight ratio of 96:2:2 in order, mix them in 40 g of NMP, and obtain a uniform slurry by vacuum stirring. Then, the slurry is evenly coated on an aluminum foil current collector, and rolled and baked in a 100° C. oven (rolling belt 2 m / min) at 10 m, vacuum baked at 85° C. for 20 h, and then cold pressed and cut to obtain a double-layer coated positive electrode sheet containing a multi-single crystal ternary positive electrode material;

[0105] (3) 100 g of artificial graphite: conductive agent Super P: CMC: SBR in a weight ratio of 95:2:1.5:1.5 were weighed in order, mixed in 40 g of deionized water, and vacuum stirred to obtain a uniform slurry. The slurry was then evenly coated on a copper foil current collector, and rolled and baked in a 100 ° C oven (rolling belt 2m / min) for 10 minutes, and vacuum baked at 85 ° C for 20 hours, and then cold pressed and cut to obtain a negative electrode sheet;

[0106] (4) stacking the positive electrode sheet, the negative electrode sheet, and the separator into a lithium-ion battery cell; placing the lithium-ion battery cell into a soft-pack battery package and injecting 1 mol / L lithium hexafluorophosphate (LiPF 6 ) of ethyl carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio), an electrolyte containing 2wt% vinylene carbonate (VC) and 3wt% 1,3-propane sultone (PS);

[0107] (5) After hot pressing, formation, cold pressing, aging, secondary sealing, and sorting, a lithium-ion battery using a double-layer coated poly single crystal ternary positive electrode material as a positive electrode active material is prepared.

[0108] Comparative Example 1

[0109] According to Li 2 CO 3 With D 50 10-20μm Ni 0.65 Co 0.15 Mn 0.25 (OH) 2 The mixture was mixed at a high speed at 300r / min with a molar ratio of Li / (Ni+Co+Mn) of 1.05:1.0; the mixture was placed in a sagger and sintered for the first time in a box furnace, with oxygen introduced as the sintering atmosphere. The synthesis was mainly carried out in three constant temperature zones, with a heating rate of 2℃ / min between each zone: 400℃ for 1h in the low temperature zone; 700℃ for 2h in the medium temperature zone; and 780℃ for 12h in the high temperature zone. The box furnace was then cooled naturally, and the coarse powder was taken out and passed through a 300-mesh sieve to obtain a secondary spherical ternary material. The scanning electron microscope image is shown in the figure. Figure 2 shown.

[0110] The secondary spherical ternary material obtained above is mixed with nano-scale Al 2 O 3 Mix well, including Al 2 O 3 With Li 1.05 Ni 0.65 Co 0.15 Mn 0.25 O 2The molar ratio is designed to be 1000ppm, and the second sintering is carried out. The temperature is raised to 600°C at 2°C / min in an oxygen atmosphere and kept warm for 10 hours. After cooling, a single-layer coated secondary spherical ternary material is obtained.

[0111] In the secondary spherical ternary material, the number of primary particles n is greater than 500, and the median particle size D of the positive electrode material is 50 The median particle size of the primary particles is 10 μm. 50 0.1-0.5μm;

[0112] Does not satisfy the relationship shown in the following equation 1: D 50 3 =K×n×d 50 3 Formula 1.

[0113] Comparative Example 2

[0114] (1) According to Li 2 CO 3 With D 50 Ni less than 10μm 0.65 Co 0.15 Mn 0.25 (OH) 2 The mixture was mixed at a high speed of 400r / min at a molar ratio of Li / (Ni+Co+Mn) of 1.05:1.0. The mixture was placed in a sagger and sintered for the first time in a box furnace, with oxygen introduced as the sintering atmosphere. It was roasted at 930°C for 24h; then the box furnace was cooled naturally, the material was taken out and crushed, and then passed through a 300-mesh sieve; then the muffle furnace was cooled naturally, the material was taken out and crushed by air flow, and then passed through a 300-mesh sieve to obtain a single-crystal ternary material, and its scanning electron microscope image is shown as follows: Figure 4 shown.

[0115] The single crystal ternary material obtained above is mixed with nano-scale Al 2 O 3 Mix well, including Al 2 O 3 With Li 1.05 Ni 0.65 Co 0.15 Mn 0.25 O 2 The molar ratio is designed to be 1000ppm, and the second sintering is carried out. It is baked at 600°C for 10 hours in an oxygen atmosphere, and a single-layer coated single-crystal ternary material is obtained after cooling.

[0116] In the single crystal ternary material, the number of primary particles n is 1, and the median particle size D of the positive electrode material is 50 The median particle size of primary particles is 3.56 μm. 50 It is 3.56μm.

[0117] Example 2

[0118] The other operations are the same as those in Example 1, except that step (1) is specifically as follows:

[0119] (1) According to Li 2 CO 3 With D 50 Ni of 3-7μm (excluding 7μm) 0.65 Co 0.15 Mn 0.25 (OH) 2 According to the molar ratio of Li / (Ni+Co+Mn) of 1.05:1, a certain amount of nano-MoO was added after high-speed mixing at 400r / min. 3 and WO 3 , continue to mix at a high speed of 400r / min, where Mo 2 O 3 The amount of Ni added accounts for 0.65 Co 0.15 Mn 0.25 (OH) 2 The molar ratio of WO is 0.25%. 3 The amount of Ni added accounts for 0.65 Co 0.15 Mn 0.25 (OH) 2 The molar ratio is 0.25%; the mixture is placed in a sagger and sintered for the first time in a box furnace, and oxygen is introduced as the sintering atmosphere. The synthesis is mainly carried out in three constant temperature zones, and the heating rate between each zone is 2℃ / min: the low temperature zone is kept at 400℃ for 1h; the medium temperature zone is kept at 700℃ for 2h; the high temperature zone is kept at 910℃ for 12h; then the box furnace is cooled naturally, the material is taken out, and it is crushed by air flow and passed through a 300-mesh screen to obtain a multi-single crystal ternary material;

[0120] In the poly-single-crystal ternary material, the number of primary particles n is 5-200, and the median particle size D of the positive electrode material is 50 The median particle size of primary particles is 3.92 μm. 50 0.15-1.3μm;

[0121] Satisfies the relationship shown in the following equation 1:

[0122] D 50 3 =K×n×d 50 3 Formula 1

[0123] Among them, K is 0.25-2.

[0124] The obtained multi-single crystal ternary material is mixed with nano-scale Al 2 O 3 Mix well, including Al 2 O 3 The mass ratio of the polysingle crystal ternary material is 1000ppm, and the second sintering is carried out. The temperature is raised to 600℃ at 2℃ / min in an oxygen atmosphere and kept for 10h. After cooling, a single-layer coated polysingle crystal ternary material is obtained. The above-obtained single-layer coated polysingle crystal ternary material is mixed with nano-scale WO 3 Mix well, including WO 3 The single-layer coated poly single crystal ternary material is designed with a mass ratio of 2500ppm and sintered for the third time. The temperature is raised to 500°C at 2°C / min in an oxygen atmosphere and kept warm for 10 hours. After cooling, a double-layer coated poly single crystal ternary material is obtained.

[0125] (a) Performance test:

[0126] (1) After the batteries of Example 1 and Comparative Examples 1-2 were left standing at 25°C for 24 hours, they were charged to 4.3V using a 0.1C rate current of the sorting capacity, and after standing for 10 minutes, they were discharged using a 0.1C rate current of the design capacity until the voltage was 3.0V. Taking the current discharge capacity as the benchmark, after standing for 10 minutes, they were charged to 4.3V using 0.1C, 0.2C, 0.5C, 1.0C, 2.0C, 5C, and 10C, and then discharged using the charging rate current until the discharge voltage was 3.0V. The interval between each charge and discharge was 10 minutes, and each rate charge and discharge cycle was repeated 5 times, and the discharge rate was calculated. The test results are shown in Table 1.

[0127] (2) The batteries of Example 1 and Comparative Examples 1-2 were placed in a constant temperature environment of 45°C for 24 hours, and then charged to 4.3V using the above-mentioned 1C rate current, and charged at a constant voltage of 4.3V with a cut-off current of 0.05C. After being placed in a constant temperature environment of 45°C for 24 hours, the batteries were discharged at the same current until the voltage was cut off at 3.0V, forming one charge and discharge cycle. After being placed in a constant temperature environment of 45°C for 10 minutes, the next cycle was carried out. The entire cycle test temperature was carried out in an environment of 45°C. The test results are shown in Table 1.

[0128] Test result description:

[0129] The data in Table 1 show that Example 1 can reach 180.1 mAh / g when discharged from the upper voltage limit of 4.3 V to 3.0 V, and has a capacity retention rate of 89.42% after 1200 cycles at this voltage and 45°C. In Example 1 and Comparative Examples 1-2, the particle size of the precursor is regulated, and Mo and W-containing substances are added during the synthesis to regulate the growth mode of the primary particles and the control of the calcination temperature so that the three morphologies of the polycrystalline, single crystal, and secondary sphere are formed respectively. Figure 3 As can be clearly seen from Table 1, under high voltage and high rate cycling at up to 4.3V, its cycle performance is higher than that of secondary spherical materials, and its rate performance is much higher than that of single crystal materials, achieving and solving the problem of whether the rate performance and cycle stability of ternary materials can be taken into account at the same time.

[0130] Table 1 Lithium ion battery performance test results of Example 1 and Comparative Examples 1-2

[0131]

[0132] (b) Performance test:

[0133] (1) The batteries of Example 2 and Comparative Example 2 were placed at room temperature of 25° C. for 24 h and then subjected to the following tests: initial DC impedance R1 and R2; discharge at a rate of 0.5C-10C, with a charge and discharge range of 2.75-4.3V; and the temperature of the discharged batteries at the rate was detected. The temperature rise results are shown in Table 2.

[0134] (2) The batteries of Example 2 and Comparative Example 2 were placed in a room temperature environment at 25° C. for 24 h, and then the following tests were performed: initial DC impedance R1 and R2; 1200 cycles at a rate of 1C, with a voltage range of 2.75-4.3 V, and the changes in DC impedance during the 1200 cycles were detected. Figure 5 shown.

[0135] Table 2: The increase in surface temperature of the cells of Example 2 and Comparative Example 2 when the batteries are discharged at the same rate under the same conditions

[0136]

[0137] Test result description:

[0138] The initial DC impedance of the battery assembled from poly-single-crystal ternary materials (Example 2) is R1=5mΩ, and the initial DC impedance of the battery assembled from single-crystal ternary materials (Comparative Example 2) is R2=23mΩ. After 1200 cycles, the growth rate of the DC internal resistance of the poly-single-crystal is at the same level as that of the single crystal.

[0139] The data in Table 2 show that with the increase of charge and discharge rate, the surface temperature of the battery shows an increasing trend, among which the temperature increase of poly single crystal is lower than that of single crystal, which once again proves that the particle morphology of poly single crystal has advantages over single crystal in temperature rise control; the data in Table 2 show that with the continuous increase of charge rate, the battery temperature of single crystal material rises significantly, while that of poly single crystal is lower than that of poly single crystal; this shows that poly single crystal ternary material has advantages over single crystal in temperature control during high rate charge and discharge.

[0140] (c) Performance testing:

[0141] Take 4 button batteries from each of the above-mentioned Example 2 and Comparative Example 1, take 1 battery and charge it from 2.8V to 4.3V cut-off voltage at a rate of 0.1C to test the full charge capacity, charge the remaining batteries to different cut-off voltages and test the capacity, that is, keep the remaining batteries charged to 4.1V, 4.2V and 4.4V, disassemble the batteries, test the DSC of the positive electrode, the initial exothermic temperature is shown in Table 3, and the peak temperature is shown in Table 4.

[0142] Table 3 Comparison of DSC initial exothermic temperature data of the positive electrode materials of Example 2 and Comparative Example 1

[0143] DSC initial temperature at different voltages ℃ 4.1V 4.2V 4.3V 4.4V Example 2 285.2 280.4 276.1 268.7 Comparative Example 1 255.7 249.6 245.3 238.6

[0144] Table 4 Comparison of DSC main exothermic peak temperature data of positive electrode materials of Example 2 and Comparative Example 1

[0145] DSC peak temperature at different voltages ℃ 4.1V 4.2V 4.3V 4.4V Example 2 289.0 284.9 280.6 278.4 Comparative Example 1 268.8 264.2 257.3 251.2

[0146] Test results: According to the data shown in Tables 3 and 4, the initial exothermic temperature and the main exothermic peak temperature of the poly single crystal are higher than those of the secondary spherical particles, indicating that the structural stability is superior to the secondary spherical morphology.

[0147] Example 3

[0148] D 50 Cobaltous oxide, nano-magnesium hydroxide and tungsten oxide powders with a size of 8-10 μm are uniformly mixed at high speed in a high-speed ball mill, wherein the added amounts of magnesium hydroxide and tungsten oxide account for 0.6wt% and 1.4wt% of the mass of cobaltous oxide respectively. Then, lithium carbonate is added to the above mixture and mixed at high speed, wherein the lithium carbonate is added at a Li / Co molar ratio of 1.05:1. After being uniformly mixed, the mixture is passed through a 300-mesh sieve to finally obtain a mixed powder.

[0149] The mixed powder was heated to 750℃ in air atmosphere at a heating rate of 5℃ / min, and kept for one hour, then switched to 2℃ / min and heated to 980℃, and kept at this temperature for 8h. The obtained sintered material was naturally cooled and then pulverized by air flow. During the pulverization process, the median particle size D50 of the material was controlled at 9-12μm, which is a multi-single-crystal lithium cobalt oxide. Its SEM image is shown as follows: Figure 6 As shown;

[0150] In the polycrystalline lithium cobalt oxide, the number of primary particles n is 3-80, and the median particle size D of the positive electrode material is 50 The median particle size of primary particles is 10.67 μm. 50 2-3μm;

[0151] Satisfies the relationship shown in the following equation 1:

[0152] D50 3 =K×n×d 50 3 Formula 1

[0153] Among them, K is 0.25-2.

[0154] The above-obtained poly single-crystal lithium cobalt oxide and nano aluminum hydroxide are uniformly mixed, wherein the aluminum hydroxide accounts for 0.15wt% of the mass of the poly single-crystal lithium cobalt oxide, to obtain a mixed powder, and the mixed powder is sintered in an air atmosphere at 960° C. for 10 hours. The obtained sintered product is naturally cooled and passed through a 300-mesh sieve to obtain a single-layer coated poly single-crystal lithium cobalt oxide positive electrode material.

[0155] The above-obtained single-layer coated poly-single-crystal lithium cobalt oxide positive electrode material and nano-zirconia are uniformly mixed, wherein the zirconium oxide accounts for 0.18wt% of the mass of the single-layer coated poly-single-crystal lithium cobalt oxide, to obtain a mixed powder, and the mixed powder is sintered in an air atmosphere at 960° C. for 10 hours. The obtained sintered product is naturally cooled and passed through a 300-mesh sieve to obtain a double-layer coated poly-single-crystal lithium cobalt oxide positive electrode material.

[0156] 100 g of the above-mentioned double-layer coated poly single crystal lithium cobalt oxide positive electrode material, conductive agent Super P, and binder PVDF were weighed in a weight ratio of 96:2:2 in order, mixed in 40 g of NMP, and vacuum stirred to obtain a uniform slurry, and then the slurry was evenly coated on the aluminum foil current collector, and rolled and baked in a 100°C oven (rolling belt 2m / min) at 10m, vacuum baked at 85°C for 20h, and then cold pressed and cut to obtain a positive electrode sheet;

[0157] 100 g of artificial graphite: conductive agent Super P: CMC: SBR were weighed in the order of 95:2:1.5:1.5 by weight, mixed in 40 g of deionized water, and vacuum stirred to obtain a uniform slurry. The slurry was then evenly coated on a copper foil current collector, and rolled and baked in a 100 ° C oven (rolling belt 2m / min) for 10 minutes, and vacuum baked at 85 ° C for 20 hours, and then cold pressed and cut to obtain a negative electrode sheet;

[0158] The positive electrode sheet, the negative electrode sheet and the separator are stacked into a lithium-ion battery cell; the lithium-ion battery cell is placed in a soft-pack battery package and injected with 1 mol / L lithium hexafluorophosphate (LiPF 6 ) of ethyl carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio), an electrolyte containing 2wt% vinylene carbonate (VC) and 3wt% 1,3-propane sultone (PS);

[0159] The lithium-ion battery is prepared through the steps of hot pressing, formation, cold pressing, aging, secondary sealing, sorting and the like.

[0160] Comparative Example 3

[0161] D 50 Cobaltous oxide and lithium carbonate with a particle size larger than 10 μm are added to the above mixture and mixed at a high speed, wherein the lithium carbonate is added at a Li / Co molar ratio of 1.05:1, and finally a mixed powder is obtained.

[0162] The mixed powder was heated to 1100°C in an air atmosphere and maintained at this temperature for 24 hours. The sintered material was naturally cooled and then pulverized by air flow to obtain single-crystal lithium cobalt oxide, as shown in the SEM image. Figure 7 As shown;

[0163] In the monocrystalline lithium cobalt oxide, the number of primary particles n is 1, and the median particle size D of the positive electrode material is 50 The median particle size of primary particles is 14.34 μm. 50 It is 14.34μm.

[0164] The monocrystalline lithium cobalt oxide and nano aluminum hydroxide obtained above are mixed evenly, wherein the aluminum hydroxide accounts for 0.3wt% of the mass of the monocrystalline lithium cobalt oxide, to obtain a mixed powder, and the mixed powder is sintered in an air atmosphere at 800°C for 16 hours. The obtained sintered product is naturally cooled and passed through a 300-mesh sieve to obtain a single-layer coated monocrystalline lithium cobalt oxide positive electrode material.

[0165] 100 g of the above-mentioned single-layer coated single-crystal lithium cobalt oxide positive electrode material, conductive agent Super P, and binder PVDF were weighed in a weight ratio of 96:2:2 in order, mixed in 40 g of NMP, and vacuum stirred to obtain a uniform slurry, and then the slurry was evenly coated on the aluminum foil current collector, and rolled and baked in a 100° C. oven at 10 m (rolling belt 2 m / min), vacuum baked at 85° C. for 20 h, and then cold pressed and cut to obtain a positive electrode sheet;

[0166] 100 g of artificial graphite: conductive agent Super P: CMC: SBR were weighed in the order of 95:2:1.5:1.5 by weight, mixed in 40 g of deionized water, and vacuum stirred to obtain a uniform slurry. The slurry was then evenly coated on a copper foil current collector, and rolled and baked in a 100 ° C oven (rolling belt 2m / min) for 10 minutes, and vacuum baked at 85 ° C for 20 hours, and then cold pressed and cut to obtain a negative electrode sheet;

[0167] The positive electrode sheet, the negative electrode sheet and the separator are stacked into a lithium-ion battery cell; the lithium-ion battery cell is placed in a soft-pack battery package and injected with an electrolyte containing 1 mol / L lithium hexafluorophosphate (LiPF6) of ethyl carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio), 2 wt% vinylene carbonate (VC) and 3 wt% 1,3-propane sultone (PS);

[0168] The lithium-ion battery is prepared through the steps of hot pressing, formation, cold pressing, aging, secondary sealing, sorting and the like.

[0169] Comparative Example 4

[0170] D 50 Cobaltous oxide and lithium carbonate with a particle size larger than 10 μm are added to the above mixture and mixed at a high speed, wherein the lithium carbonate is added at a Li / Co molar ratio of 1.05:1, and finally a mixed powder is obtained.

[0171] The mixed powder was heated to 900°C in an air atmosphere and maintained at this temperature for 24 hours. After natural cooling and sieving, secondary spherical lithium cobalt oxide was obtained. Its SEM image is shown in Figure 8 As shown; after pulverizing, a polycrystalline primary sintered lithium cobalt oxide formed by agglomeration of multiple primary single crystal particles is obtained, and the number of single crystal particles is ≥500;

[0172] In the secondary spherical lithium cobalt oxide, the number of primary particles n is greater than 500, and the median particle size D of the positive electrode material is 50 The median particle size of primary particles is 9.54 μm. 50 0.5-2μm;

[0173] Does not satisfy the relationship shown in the following equation 1: D 50 3 =K×n×d 50 3 Formula 1.

[0174] The secondary spherical lithium cobalt oxide and nano aluminum hydroxide obtained above are mixed evenly, wherein the aluminum hydroxide accounts for 0.3wt% of the mass of the lithium cobalt oxide, to obtain a mixed powder, and the mixed powder is sintered in an air atmosphere at 820°C for 16 hours. The obtained sintered product is naturally cooled and passed through a 300-mesh sieve to obtain a single-layer coated secondary spherical lithium cobalt oxide positive electrode material.

[0175] 100 g of the above-mentioned single-layer coated secondary spherical lithium cobalt oxide positive electrode material, conductive agent Super P, and binder PVDF were weighed in a weight ratio of 96:2:2 in order, mixed in 40 g of NMP, and vacuum stirred to obtain a uniform slurry, and then the slurry was evenly coated on the aluminum foil current collector, and rolled and baked in a 100°C oven (rolling belt 2m / min) at 10m, vacuum baked at 85°C for 20h, and then cold pressed and cut to obtain a positive electrode sheet;

[0176] 100 g of artificial graphite: conductive agent Super P: CMC: SBR were weighed in the order of 95:2:1.5:1.5 by weight, mixed in 40 g of deionized water, and vacuum stirred to obtain a uniform slurry. The slurry was then evenly coated on a copper foil current collector, and rolled and baked in a 100 ° C oven (rolling belt 2m / min) for 10 minutes, and vacuum baked at 85 ° C for 20 hours, and then cold pressed and cut to obtain a negative electrode sheet;

[0177] The positive electrode sheet, the negative electrode sheet and the separator are stacked into a lithium-ion battery cell; the lithium-ion battery cell is placed in a soft-pack battery package and injected with 1 mol / L lithium hexafluorophosphate (LiPF 6 ) of ethyl carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio), an electrolyte containing 2wt% vinylene carbonate (VC) and 3wt% 1,3-propane sultone (PS);

[0178] The lithium-ion battery is prepared through the steps of hot pressing, formation, cold pressing, aging, secondary sealing, sorting and the like.

[0179] Table 5 Performance test results of the batteries of Example 3 and Comparative Examples 3-4

[0180]

[0181] The results in Table 5 show that poly-single-crystal lithium cobalt oxide has an advantage over single-crystal lithium cobalt oxide in terms of gram capacity, and has a more obvious advantage over secondary balls in terms of normal temperature cycling at 25°C.

[0182] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises a plurality of particles with a polymeric single crystal morphology, wherein the particles with a polymeric single crystal morphology are formed by nesting a plurality of primary particles, that is, a primary particle in the particles with a polymeric single crystal morphology is fused and connected with a plurality of primary particles through an internal driving force to form a surrounding structure nested with each other; the positive electrode material satisfies the relationship shown in the following formula 1: D 50 3 =K×n×d 50 3 Formula 1 Wherein, K is the coefficient, and its range is: 0.2≤K≤2; n is the number of primary particles, and its range is: 2≤n≤500; D 50 is the median particle size of the positive electrode material, in μm; d 50 is the median particle size of primary particles, in μm; The median particle size d of the primary particles 50 0.1μm-2μm; The primary particles are ternary materials; The median particle size D of the positive electrode material 50 0.2μm-9μm.

2. The positive electrode material according to claim 1, characterized in that Particles with a polycrystalline morphology were prepared using D 50 The precursor of the ternary material with a size of <7μm was prepared.

3. The positive electrode material according to claim 1, characterized in that The chemical formula of the ternary material is Li a Ni 1-x-y- p Co x M 1 y M 2 p O2, 0.95≤a<1.08, 0.5≤1-xyp<1.0, 0 <x≤0.3,0<y≤0.2,0<p≤0.005;M 1 Mn or Al, M 2 It is one or more of Mg, Sr, Ba, Y, W, Nb, and Mo.

4. A positive electrode material, characterized in that The positive electrode material comprises a plurality of particles with a polymeric single crystal morphology, wherein the particles with a polymeric single crystal morphology are formed by nesting a plurality of primary particles, that is, a primary particle in the particles with a polymeric single crystal morphology is fused and connected with a plurality of primary particles through an internal driving force to form a surrounding structure nested with each other; the positive electrode material satisfies the relationship shown in the following formula 1: D 50 3 =K×n×d 50 3 Formula 1 Wherein, K is the coefficient, and its range is: 0.2≤K≤2; n is the number of primary particles, and its range is: 2≤n≤500; D 50 is the median particle size of the positive electrode material, in μm; d 50 is the median particle size of primary particles, in μm; The median particle size d of the primary particles 50 2μm-3μm; The primary particles are lithium cobalt oxide; The median particle size D of the positive electrode material 50 10μm-20μm.

5. The positive electrode material according to claim 4, characterized in that The chemical formula of the lithium cobalt oxide is Li a Co 1-b M b O2, wherein M is one or more of Al, W, Mg, Ti, Zr, Y, Ce, Mo, 0.95≤a≤1.07, 0 <b≤0.1。 6. The positive electrode material according to any one of claims 1 to 5, characterized in that The positive electrode material further comprises a coating layer, and the coating layer is coated on the surface of a plurality of particles having a multi-single crystal morphology; The mass of the coating layer accounts for 0.05-0.5wt% of the total mass of the positive electrode material.

7. The positive electrode material according to claim 6, characterized in that The coating layer includes a first coating layer and a second coating layer, the first coating layer is coated on the surface of several particles with a multi-single crystal morphology, and the second coating layer is coated on the outer surface of the first coating layer. The first coating layer is a metal compound, and the second coating layer is a metal compound and / or a non-metal compound.

8. A positive electrode sheet, comprising the positive electrode material according to any one of claims 1 to 7.

9. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 7 or the positive electrode sheet according to claim 8.

Citation Information

Patent Citations

  • Cathode material and preparation method thereof, and battery

    CN110165205A

  • Positive active material for rechargeable lithium battery, method of preparing the same and rechargeable lithium battery including the same

    CN111697224A